Faktor-Faktor Yang Mempengaruhi Keputusan Pembelian Pelanggan di Apotek: Tinjauan Sistematis Literatur - Shalmantyas, Fikri; Sari, Seftika; Riski, Merisa (Jurnal Kesehatan Saelmakers PERDANA (JKSP), 2025)
Increasingly fierce competition in the pharmacy industry demands a thorough understanding of the factors influencing customer purchasing decisions. This study aims to identify and evaluate the key factors influencing purchasing decisions in pharmacies through a systematic literature review. The method used was a systematic review following the PRISMA guidelines and the PICO framework. A search was conducted through the Google Scholar database and e-journals with keywords related to pharmacy, customers, and purchasing. Of the 300 articles identified, 11 journals (2015–2025) met the inclusion criteria and were analyzed in depth. The review results indicated that price and service quality were the most dominant factors (36%), followed by pharmacy image or brand image (27%), and other factors such as product diversity, psychological aspects, and halal labels (9% each). The study also revealed that purchasing decisions are influenced by a combination of rational (price, product availability) and emotional (trust, convenience, religiosity) aspects. In conclusion, pharmacy managers need to develop service and marketing strategies based on consumer preferences, emphasizing quality service, trust, and strengthening product image and value